2010
DOI: 10.1111/j.1469-0691.2009.02837.x
|View full text |Cite
|
Sign up to set email alerts
|

Cationic compounds with activity against multidrug-resistant bacteria: interest of a new compound compared with two older antiseptics, hexamidine and chlorhexidine

Abstract: Use of antiseptics and disinfectants is essential in infection control practices in hospital and other healthcare settings. In this study, the in vitro activity of a new promising compound, para-guanidinoethylcalix[4]arene (Cx1), has been evaluated in comparison with hexamidine (HX) and chlorhexidine (CHX), two older cationic antiseptics. The MICs for 69 clinical isolates comprising methicillin-resistant Staphylococcus aureus, methicillin-sensitive S. aureus, coagulase-negative staphylococci (CoNS) (with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 18 publications
5
35
0
1
Order By: Relevance
“…Cationic compounds act by binding to the negatively charged surfaces of the bacterial cell wall and membranes. The results of that study showed that two strains of MDR S. maltophilia demonstrated susceptibility to CHX (MIC Ͻ 1 to 32 mg/ liter), some susceptibility to HX (MIC ϭ 32 to 256 mg/liter), and resistance to CxI (MIC ϭ 256 mg/liter) (132).…”
Section: New Treatment Strategiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Cationic compounds act by binding to the negatively charged surfaces of the bacterial cell wall and membranes. The results of that study showed that two strains of MDR S. maltophilia demonstrated susceptibility to CHX (MIC Ͻ 1 to 32 mg/ liter), some susceptibility to HX (MIC ϭ 32 to 256 mg/liter), and resistance to CxI (MIC ϭ 256 mg/liter) (132).…”
Section: New Treatment Strategiesmentioning
confidence: 91%
“…The antibacterial activities of new cationic compounds (e.g., hexamidine diisethionate [HX], chlorhexidine digluconate [CHX], and para-guanidinoethylcalix [4]arene [CxI]) have been assessed (132). Cationic compounds act by binding to the negatively charged surfaces of the bacterial cell wall and membranes.…”
Section: New Treatment Strategiesmentioning
confidence: 99%
“…More importantly, it has been noted that guanidine-based polymers can overcome bacterial resistance [27,28]. Polyhexamethylene guanidine hydrochloride (PHGH) has been known to exhibit antimicrobial property for years.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies with limited data have been performed with either E. coli or K. pneumoniae, and less is known in the case of clinical isolates (19,(22)(23)(24)(25)(26)(27). The aim of this study was to determine the effect of preexposure to the more commonly used biocides in hospitals and domestic settings (TRI, CHX, benzalkonium chloride [BKC], and sodium hypochlorite [SHC]), or to antibiotics of wide consumption (ampicillin [AMP] and ciprofloxacin [CIP]) on the selection of biocide-resistant variants and to explore the associated changes in metabolism and bacterial growth rate.…”
mentioning
confidence: 99%